Face perception in the Japanese population using EEG - Miki, Kensaku; Takeshima, Yasuyuki; Watanabe, Shoko; Kakigi, Ryusuke (Frontiers in Psychology, 2025)
The face contains abundant information and plays an important role in our interactive communication. Electroencephalography (EEG) has excellent temporal resolution, making it a useful tool for investigating the time-sequence of face perception processes. Studies on development, conducted in Western populations, found that event-related potential (ERP) changes in children begin in mid-childhood. However, there are few studies on developmental changes in Japanese children. In addition, few studies have investigated whether hospitality expertise affects these processes in Western and Japanese populations. In this review, we summarize evidence from EEG studies that investigated face perception processes, with a focus on three developmental and expertise-related studies with Japanese participants. These findings are compared with studies involving Western participants to explore the influence of cultural and experiential factors on face-related brain responses. The face detection pattern in 13-year-old Japanese children is similar to that in adults. This suggests that face detection matures at this age in the Japanese population, differing from findings in Western populations. In addition, few studies have investigated the face emotional change perception process in Western and Japanese populations. However, ERP patterns in response to facial emotional changes in Japanese children aged 7–14 differs from that in adults. This suggests that the process of perceiving facial emotional changes in the Japanese population does not fully mature by the age of 14. Moreover, facial emotion perception in the Japanese population may be influenced by hospitality expertise. We propose the following hypotheses based on this review: (1) the age of maturation for face detection and facial emotional change perception processes are different, (2) expertise may increase attention to emotion and affect the early stage of the face perception process due to training and experience, and (3) the face perception process in the Japanese population differs from that in Western populations.